Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00167-004-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of posterior stability in total knee replacement by stress radiographs

Abstract: The aim of this study was to assess the posterior stability of two different designs of total knee replacement (TKR) with deep-dished mobile bearing (MB) implants using stress X-rays. In a prospective non-randomized consecutive study, 34 patients with primary osteoarthritis of the knee underwent TKR. In group A (17 knees), they received a MB insert with a Duracon prosthesis and in group B (18 knees), a Genesis prosthesis. In all cases the posterior cruciate ligament (PCL) was resected. All patients had pre- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In the lateral stress view according to the kneeling method [96], the patient knees on a bench with the knee at 90° of flexion; the bench only supports the lower legs up to the tibial tubercle. In this position a lateral X-ray is taken [96].…”
Section: Imagingmentioning
confidence: 99%
“…In the lateral stress view according to the kneeling method [96], the patient knees on a bench with the knee at 90° of flexion; the bench only supports the lower legs up to the tibial tubercle. In this position a lateral X-ray is taken [96].…”
Section: Imagingmentioning
confidence: 99%
“…Although new measurement methods without a stress device are being introduced, such as the kneeling position suggested by Louisia et al 19 and supine lateral radiography as described by Kim et al, 15 stress radiography with a Telos device remains the most frequently used method for assessing PCL injuries, grading instability, and evaluating treatment outcomes owing to its reproducibility, quantifiability, and easy application in daily clinical settings. 14 , 20 However, no consensus has been reached regarding the posterior drawer force (89-150 N) 12 , 14 position that provides the optimal method to measure instability.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques to quantify posterior instability are available, including stress radiography using a stress device, kneeling position, supine lateral radiography, and arthrometry. 11 , 12 , 14 , 15 , 19 , 24 In PCL injury, stress radiography is generally accepted to be superior in quantifying posterior instability. 10 , 12 , 22 However, the reliability of this measurement method has not been well-evaluated in a larger patient population, and no clear standard method has been established.…”
mentioning
confidence: 99%
“…In a comparison study by Jung et al, 11 the Telos device, hamstring contraction, 3 kneeling view, 8,13,14 gravity view, 21,22 and axial view 15 stress radiography techniques were assessed based on PTD, time per radiograph, and patient pain. The authors concluded that the Telos method and kneeling view produced the largest PTD values.…”
mentioning
confidence: 99%
“…This potential reduction in PTD from pain-related muscular activation or weight shifting may therefore inappropriately alter management decisions that are based on the results of the PCL stress radiographs. 11,18 In a comparison study by Jung et al, 11 the Telos device, hamstring contraction, 3 kneeling view, 8,13,14 gravity view, 21,22 and axial view 15 stress radiography techniques were assessed based on PTD, time per radiograph, and patient pain. The authors concluded that the Telos method and kneeling view produced the largest PTD values.…”
mentioning
confidence: 99%